2014
DOI: 10.1111/fwb.12384
|View full text |Cite
|
Sign up to set email alerts
|

Modelling occupancy of an imperilled stream fish at multiple scales while accounting for imperfect detection: implications for conservation

Abstract: Summary Predictive models of species distribution are useful tools to identify habitats of imperilled species for protection, inventory and restoration. Critical aspects of such models include the influence of scale, uncertainties associated with imperfect detection and spatial autocorrelation and transferability of model predictions. We addressed these issues in developing occupancy models of the imperilled eastern sand darter (Ammocrypta pellucida) based on surveys of the Grand and Thames Rivers, Ontario, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 61 publications
(77 reference statements)
2
45
0
Order By: Relevance
“…Species distribution models notoriously perform badly with imperfect detection26. Occupancy models that account for imperfect detection are therefore gaining popularity (see for instance27) but they are not always better at predicting species distribution28. This is why decreasing false negatives created by imperfect detection remains the most effective way of getting accurate distributions.…”
Section: Discussionmentioning
confidence: 99%
“…Species distribution models notoriously perform badly with imperfect detection26. Occupancy models that account for imperfect detection are therefore gaining popularity (see for instance27) but they are not always better at predicting species distribution28. This is why decreasing false negatives created by imperfect detection remains the most effective way of getting accurate distributions.…”
Section: Discussionmentioning
confidence: 99%
“…To account for potential spatial structuring in species occurrence patterns (Dormann , Dextrase et al , Huang and Frimpong ), we applied a distance‐based Moran's Eigenvector maps approach (Borcard and Legendre , Dray et al , Blanchet et al , Legendre and Gauthier ). This approach is conceptually similar to Fourier analysis, which explains the variability of an observed pattern via a combination of trigonometric‐curves with multiple scales (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Sand darters are habitat specialists and thus sensitive to habitat alterations, which is why both species are often valued as indicators of ecosystem integrity (Grandmaison et al 2004;Drake et al 2008). Habitat use and sand grain size preference is well documented for the eastern sand darter (Daniels 1993;Facey & O'Brien 2004;Drake et al 2008;O'Brien & Facey 2008;Tessler et al 2012;Dextrase et al 2014), but literature pertaining to the western sand darter is sparse, and little information is available from areas where the two species are sympatric.…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory studies that investigated eastern sand darter substrate use reported that individuals generally used medium (0.25-0.5 mm) sized particles (Daniels 1993;O'Brien & Facey 2008). Furthermore, field surveys revealed that the species was commonly detected in sand comprised of fine to medium (0.12-0.5 mm) particles, while few individuals were detected in areas where the particle size was larger than 1.0 mm (Facey & O'Brien 2004;Tessler et al 2012;Dextrase et al 2014). Pflieger (1971) noted that in Missouri the western sand darter avoided strong currents, inhabiting shallow backwater areas, as well as quiet margins of a drainage canal at depths up to 1.5 m. Simon et al (1992) observed the western sand darter spawning and described the habitat as an area on the downstream side of an island with a slow current over coarse sand.…”
Section: Introductionmentioning
confidence: 99%